MYCOBACTERIUM TUBERCULOSIS DAN PCR - Yuyun Widaningsih; Ismawati Amin; Nurhayana Sennang; Uleng Bahrun; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
TB’s coinfection in HIV and AIDS is on the increase together with the high mortality rate. The disseminated TB infection (in blood) of HIV and AIDS patients in Africa (2005) is about 10−25%. The aim of this study was to identify M.tb disseminated infection in HIV and AIDS patients. In this study was done in six HIV and AIDS patients suffering from suspected TB co infection. The sputum was tested using Fast Acid Bacilli and culture (using LJ and MGIT media) and DST. The identification of M.tb in blood used PCR with IS6110 primer (123 bp). The study was done at Dr. Wahidin Sudirohusodo Hospital, Labuang Baji Hospital, NEHCRI and at the Biomolecular Laboratory of the Medical Faculty, Hasanuddin University. From the six patients, four of them had CD4<50 sel/μL, two patients had FAB positive, three patients had positive LJ culture on day 41–47, three patients had positive MGIT culture on day 9–47 and four patients had positive PCR. In this study there was one case of negative FAB but LJ, MGIT and PCR were positive. There were two cases with positive FAB, culture and PCR, one case with negative FAB and culture but positive PCR. The M.tb disseminated infection was 66.7% in six HIV and AIDS patients.